LITERARY TRANSLATION AND CULTURE - Botirova, Hakima (Журнал иностранных языков и лингвистики, 2021)
This article is about literary translation and culture. It analyzes translation experience, quality, level, practical significance of translations, impact on students, socio-aesthetic aspects, all-round influence on the language of translation (expanding the vocabulary, filling it with new concepts, terms, terms, increasing the power of expressive and emotional impact). it opens up new frontiers, significantly activates and accelerates socio-cultural processes.